2018
DOI: 10.48550/arxiv.1808.06723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modes of Information Flow

Abstract: Information flow between components of a system takes many forms and is key to understanding the organization and functioning of large-scale, complex systems. We demonstrate three modalities of information flow from time series X to time series Y . Intrinsic information flow exists when the past of X is individually predictive of the present of Y , independent of Y 's past; this is most commonly considered information flow. Shared information flow exists when X's past is predictive of Y 's present in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 25 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…3 as a more concrete example to draw out such differences. 4 Table I gives the measures' decomposition values. Interestingly, I min agrees with I proj , while I ccs agrees with I BROJA .…”
Section: Examples and Comparisonsmentioning
confidence: 99%
“…3 as a more concrete example to draw out such differences. 4 Table I gives the measures' decomposition values. Interestingly, I min agrees with I proj , while I ccs agrees with I BROJA .…”
Section: Examples and Comparisonsmentioning
confidence: 99%
“…Rephrasing James et al [19], transfer entropy is sensitive to both intrinsic dependencies between Z t and Y t+1 , as well as the dependencies induced by Y t . To filter the latter dependencies and precisely measure information flow, Sattari et al [21] proposed the use of intrinsic mutual information from Z to Y, defined as…”
Section: Background On Information-theoretic Metrics For Causal Analysismentioning
confidence: 87%
“…Building on this key limitation, James et al [19] have recently detailed information flow within a pair of dynamical systems, distinguishing multiple, co-existing modalities of information flow that have been erroneously compounded in the literature. Among them, 'intrinsic information flow' pertains to the predictive power that the present of the source alone has on the target's future, independent of the target's present: this quantity is what is routinely referred to as information flow (but seldom precisely measured).…”
Section: Introductionmentioning
confidence: 99%
“…Using a simple binary model, it was demonstrated that the transfer entropy between two processes is not localized in the way that the expression of "transfer from one to another" [73], hence transfer entropy is not appropriate to characterize 'information flow' in some cases. However, in recent works [17,74], it is shown that transfer entropy can be decomposed into two distinct modes of information flow, namely intrinsic and synergistic. This intrinsic information from X to Y is designed to extract solely the information flow from X to Y, buried in transfer entropy.…”
Section: Discussionmentioning
confidence: 99%